2016
DOI: 10.1080/00131911.2016.1213224
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the legitimacy of a school’s claim to be “International”: the provision of an international curriculum as the institutional primary task

Abstract: The recent growth in the number and diversity of schools around the world classified as 'International Schools' raises questions about what makes a school's claim to be an International School legitimate. From the analysis we report here, the provision of an international curriculum emerges as what a school must do to be legitimate as an International School. It is an International School's primary task and those in such a school ideally undertake institutional work on that task. We consequently bring the idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 29 publications
(30 reference statements)
0
45
0
Order By: Relevance
“…Although the strength of this definition and categorisation of international schools is not known for certain, it has been arguably reinforced by the way it is now deemed quite ‘normal’ in the trade and popular press to refer to the ‘growing English-medium international schools market’ (eg Marsh, 2017). Put another way, a school in Bangkok, for example, that delivers a non-Thai curriculum in English can identify as an international school even though there is a strong argument for saying that the delivery of an international curriculum that promotes the values, skills, and dispositions of ‘international mindedness’ would give it greater legitimacy as an institution (Bunnell, Fertig, and James, 2018). It also diminishes the role that having a diverse body of teachers from a range of national cultures would have; ‘diversity’ is not a criterion for identification as an international school even though some academic commentators might argue it is a crucial factor, whilst research into international mindedness in practice (Barratt Hacking et al, 2018) has shown diversity to be highly significant.…”
Section: Exploring the Enduring Discriminationmentioning
confidence: 99%
“…Although the strength of this definition and categorisation of international schools is not known for certain, it has been arguably reinforced by the way it is now deemed quite ‘normal’ in the trade and popular press to refer to the ‘growing English-medium international schools market’ (eg Marsh, 2017). Put another way, a school in Bangkok, for example, that delivers a non-Thai curriculum in English can identify as an international school even though there is a strong argument for saying that the delivery of an international curriculum that promotes the values, skills, and dispositions of ‘international mindedness’ would give it greater legitimacy as an institution (Bunnell, Fertig, and James, 2018). It also diminishes the role that having a diverse body of teachers from a range of national cultures would have; ‘diversity’ is not a criterion for identification as an international school even though some academic commentators might argue it is a crucial factor, whilst research into international mindedness in practice (Barratt Hacking et al, 2018) has shown diversity to be highly significant.…”
Section: Exploring the Enduring Discriminationmentioning
confidence: 99%
“…Schools often achieve this through activities such as Model United Nations, Global Issues Network, European Youth Parliament and so on to promote IM. Bunnell, Fertig, and James (2017) explain that such extracurricular activities 'relate directly to the institutional primary task of providing an international curriculum' (311). Other than internationalising the school, Akin, Calik, and Engin-Demir (2017) suggest that 'active participation of students in solving the community problems .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term human rights logic is not used by the IB itself or its commentators, although research that draws on institutional theory is in evidence within the field (Bunnell, Fertig, & James, 2016, 2017a, 2017b). Institutional theory has been used to explore the legitimacy of international schools, using the concept of the primary task (Bunnell et al, 2017a).…”
Section: Institutional Logicsmentioning
confidence: 99%
“…The term human rights logic is not used by the IB itself or its commentators, although research that draws on institutional theory is in evidence within the field (Bunnell, Fertig, & James, 2016, 2017a, 2017b). Institutional theory has been used to explore the legitimacy of international schools, using the concept of the primary task (Bunnell et al, 2017a). The institutional logics perspective contributes to this as it explores the institutional pluralism of organisations such as the IB as they become embedded in sometimes competing and conflicting logics (Kraatz & Block, 2008; Pache & Santos, 2013).…”
Section: Institutional Logicsmentioning
confidence: 99%